2020
DOI: 10.1177/0363546520974370
|View full text |Cite
|
Sign up to set email alerts
|

Age and Outcomes in Hip Arthroscopy for Femoroacetabular Impingement: A Comparison Across 3 Age Groups

Abstract: Background: Limited evidence exists concerning the effect of age on hip arthroscopy outcomes for femoroacetabular impingement (FAI). Purpose/Hypothesis: The purpose was to investigate patient-reported outcomes (PROs) and clinical failure rates across various age groups in patients undergoing hip arthroscopy for FAI. We hypothesized that older patients would experience lower improvements in PROs and higher clinical failure rates. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 109 of 130 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
3
17
3
Order By: Relevance
“…This may have been in part due to the relatively small number of THR conversions, which underpowered the analysis. Although it is generally accepted that older age and the presence of OA may increase the risk of THR conversion, 17,24,29,32 in the current study where patients with Tönnis grades 2 and 3 were excluded, there was no correlation with increasing age and higher THR conversion rates. This would suggest that in the absence of OA, age may be less of a factor than was previously thought.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This may have been in part due to the relatively small number of THR conversions, which underpowered the analysis. Although it is generally accepted that older age and the presence of OA may increase the risk of THR conversion, 17,24,29,32 in the current study where patients with Tönnis grades 2 and 3 were excluded, there was no correlation with increasing age and higher THR conversion rates. This would suggest that in the absence of OA, age may be less of a factor than was previously thought.…”
Section: Discussioncontrasting
confidence: 61%
“…Predicting the likelihood of eventual failure and conversion to THR is necessary for clinical decision making. Some predictors of failure have been described previously and include age, 24 sex, 54 prolonged symptom duration and pain, 35 and more significant degenerative changes in the joint at the time of intervention. 7,44 The primary aim of this study was to report on the survivorship and clinical outcome of hip arthroscopy for symptomatic FAI at 10 years after intervention and to determine both patient characteristics and pathological parameters likely to predict failure.…”
mentioning
confidence: 91%
“… 19 As a result, there is a risk of providing misleading results if studies include pooling of patients with a wide age range. 20 , 21 , 22 Furthermore, evaluating the current clinical treatment in young elite athletes with a high rate of return to sports is of great importance.…”
mentioning
confidence: 99%
“…At 10 years postoperatively the investigators noted a 10% revision rate, all cases of which involved female patients, that was significantly associated with global laxity and preoperative symptom duration. In a second study, Lin et al 13 report 71% 5-year survival in 109 patients, with failure defined as revision surgery or progression to arthroplasty. When they divided their patients into cohorts aged 15-34, 35-50, and 51-75, the investigators found that the oldest group was 5 times more likely to progress to arthroplasty.…”
mentioning
confidence: 99%
“…Much additional clinical hip arthroscopy research has sought to identify other factors that might predict surgical outcomes, including general patient characteristics, preoperative hip anatomy, and preoperative or early postoperative pain or PROM levels. 5,11,13,[17][18][19][20] Most of these studies have been retrospective in design, so they identify associations that would need to be verified as truly predictive in future prospective studies. As New York Yankee great Yogi Berra is reported to have said, ''It's tough to make predictions, especially about the future.''…”
mentioning
confidence: 99%